Readings for social studies in elementary education - Jarolimek, John ;Walsh, Huber M. (New York : The MacMillan Company, 1965)
It is a common practice for instructors in social studies curriculum and methods courses to require students to sample some of the periodical literature relative to this field. In so doing, the student acquaints himself with current thinking and practices in social studies education. He also becomes familiar with the thinking and point of view of others besides his instructor and the author of the text used in the course. The practice of requiring such outside reading needs no defense as a sound instructional procedure.
Section 1. The Role of social studies in the elementary school -- Section 2. Developing social studies understandings, attitudes, and skills -- Section 3. Instructional processes in social studies education -- Section 4. Citizenship education -- Section 5. Building world understanding -- Section 6. Evaluating social studies learnings.
Includes bibliographical references.
Keywords: SOCIAL STUDIES